The Correlation of Neutrophil-Lymphocyte Ratio (NLR) and the Response Evaluation Criteria in Solid Tumors (RECIST) in Non-small Cell Lung Cancer (NSCLC) Patient - Andayani, Novita; Arliny, Yunita (http://dharmais.co.id/, 2024)
Background: The biological marker Neutrophil-Lymphocyte Ratio (NLR) is still being studied for its effectiveness as a predictor of prognosis and treatment response to cancer. This study aims to assess the effectiveness of the NLR as a prognostic biomarker in Non-small Cell Lung Cancer (NSCLC) patients. Methods: This observational study with a cross-sectional design intends to determine the effect of NLR on the response to the treatment of the patients as measured by Response Evaluation Criteria in Solid Tumors (RECIST). The samples collected were advanced-stage NSCLC patients who underwent chemotherapy from January 2021 to December 2022 to assess the prognosis and its relationship with NLR. The area Under the Curve Receiver Operating Characteristic (AUC ROC) curve was used to see the sensitivity, specificity, and cut-off point. Results: Sixty-seven samples met the criteria of the samples’ study. The best NLR cut-off point was 4.335 with a sensitivity of 86.7% and a specificity of 55.5%. The AUC value was 0.701 with a significance of 0.019. NLR values above the cut-off point were more frequently found in patients with progressive disease (29 samples; 43.3%). Conclusions: This study showed that there was a relationship between NLR and RECIST in NSCLC patients. NLR was quite effective as a prognostic biomarker of NSCLC patients who underwent chemotherapy.